EVALUASI CARA PRODUKSI PANGAN OLAHAN YANG BAIK PADA UMKM KERUPUK SAMILER, KELURAHAN KARANG PILANG, SURABAYA - Pamungkas, Andhika Ressa; Alfarenza M, Achmad Gaudi; Rachmawati, Farikha (Gapenas Publisher, 2025)
Food MSMEs play an essential role in promoting local economic growth, including Bu Nurahayu's MSME in Karangpilang, Surabaya, which produces kerupuk samiler. However, to enhance competitiveness and ensure product safety, the implementation of Good Processed Food Production Practices (CPPOB) is required. This activity aimed to evaluate and assist in CPPOB implementation in the targeted MSME. The methods included survey, structured interview, field observation, and evaluation based on 12 of 18 CPPOB indicators. The results absence of handwashing facilities, protective gear usage, and packaging labels. Improvements were made by installing sanitation facilities, training on personal protective showed that most indicators were met, while several deficiencies were identified such as the equipment, providing measuring tools, preparing guidebooks, and labeling products. This program effectively improved the MSME owner's understanding of sanitation and production standards and upgraded production facilities. Therefore, the assistance successfully enhanced product quality, safety, and the MSMEs readiness to meet legal standards.